Analysis of the Effect of Using a Natural Water Filter on the Efficiency of Household Expenditure and Customer Satisfaction at Perumda Tirtanadi in Hamparan Perak Sub-District - Ruri Prihatini Lubis; Muheri Indra Aja Nasution (SEAN Institute, 2026)
Clean water is a basic human need that plays a vital role in supporting health, comfort, and quality of life. Although piped water services are available through Perumda Tirtanadi, some customers still undergo additional treatment using natural water filters to improve respondents' perceptions of the quality of their daily water use. In addition to improving respondents' perceptions of water quality, the use of natural water filters also has the potential to provide economic benefits through savings on household expenses and increased customer satisfaction with clean water services. This study aims to analyze the effect of the use of natural water filters on household water expenditure efficiency and customer satisfaction at Perumda Tirtanadi in Hamparan Perak District. The study used a quantitative approach with descriptive and explanatory methods. Data were obtained by distributing questionnaires to 100 respondents selected using a purposive sampling technique. Data analysis was performed using descriptive statistics and natural linear regression. The results showed that the utilization rate of natural water filters was in the high category with an average value of 4.14. Household expenditure efficiency was also in the high category with an average value of 4.02, while the level of customer satisfaction had an average value of 3.90. The results of the regression analysis indicate that the use of natural water filters has a positive and significant effect on household expenditure efficiency and customer satisfaction with a significance value of less than 0.05. These findings indicate that the use of natural water filters can be an effective alternative to improve respondents' perceptions of the quality of water used by the community, reduce household expenditure, and increase customer satisfaction with Perumda Tirtanadi services. Therefore, the use of natural water filters can support efforts to provide more efficient and sustainable clean water at the household level.